PENGGUNAAN MEDIA INTERACTIVE FLAT PANEL (IFP) DALAM MENINGKATKAN MOTIVASI BELAJAR MURID - Siti Sarah Nabillah; Aldo Harjunanto (LPMP Provinsi DKI Jakarta, 2026)
Abstract. To raise the standard of instruction in schools in the technologically advanced 21st century, education must innovate. The usage of the Interactive Flat Panel (IFP) as a learning tool is one of the new developments; it has many benefits for making the teaching and learning process more dynamic and interesting. The purpose of this research is to investigate how the usage of Interactive Flat Panel (IFP) may boost students' enthusiasm to learn at SDN Cipinang Besar Utara 01, which has struggled with student engagement and active involvement. The study used a descriptive qualitative methodology, gathering information via documentation, interviews, and observation. The research looks at how kids' desire to learn is affected by the usage of IFP as an interactive learning medium in primary schools, which is currently comparatively rare. The findings show that using IFP greatly boosts students' interest in learning, promotes active engagement, and improves their drive to study. Additionally, IFP makes it easier for pupils to get educational content in a way that is more visually appealing and simple to comprehend. Based on these results, it is advised that educational policies promote the wider use of IFP in primary schools by giving teachers extensive training and sufficient resources to guarantee the best possible use of technology in the classroom. Keywords: Interactive Flat Panel (IFP), learning motivation, educational technology, interactive learning, elementary school.